Potential energy savings by application of the novel CRIMSON aluminium casting process - Dai, Xiaojun J.; Jolly, Mark R. (Elsevier Science B.V., Amsterdam., 2012)
Compared with its output the casting industry uses a disproportionate amount of energy as a result of the inefficient processes used. This paper presents the melting processes that are used in one of the traditional foundries and identifies the energy burdens associated with them. A comparison is then made with the novel CRIMSON process to demonstrate where energy savings can be made. An actual case or casting sample is investigated to demonstrate the advantage of energy saving in novel CRIMSON method which will help the foundry industry in reduction of energy cost and promote competitiveness in the production of high end casting components.
Keywords: Energy saving; Aluminium casting; Melting; CRIMSON